Understanding Primary School Students' Engagement with Mobile-Based Games: Insights into Learning Implications - Ulfa Khoirotul Rosidah; Supartinah Supartinah; Sekar Purbarini Kawuryan (AL-ISHLAH: Jurnal Pendidikan, 2025)
Mobile-based games have become integral to children's daily lives, particularly among primary school students, serving not only as entertainment but also as potential learning tools. This study aims to identify the types of mobile-based games frequently played by primary students and analyze their contribution to learning outcomes. A descriptive quantitative approach was employed, involving 69 fourth-grade students from three primary schools. Data were collected through questionnaires and interviews to capture students' gaming habits and perceptions of their learning experiences. The findings reveal that all participants (100%) have engaged with mobile-based games, with 52 different game types recorded. Action (77%) and adventure (36%) categories emerged as the most popular. Notably, 86% of students reported playing games related to school subjects. These educational games were found to enhance student engagement, foster creativity, and make learning more enjoyable. Specifically, 55% of students rated learning through games as enjoyable, while 42% considered it somewhat enjoyable. The study demonstrates the significant role mobile-based games play in supporting learning, indicating their potential to complement traditional teaching methods. However, the study is limited to a small sample size and specific grade level, suggesting the need for broader research. Future studies should explore the development of structured game-based learning frameworks and encourage collaboration between educators and game developers to design effective educational tools tailored to students' interests.